Triple Negative Breast Tumors In Iraqi Women - Faisal Ali Lattef1, Noor Fouad Mohamed Ali2, Basim Mohammed Abdulmajeed3, Ahmed Salahuddin Mohammed4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Breast cancer is heterogeneous disease. From this; a special group of tumors, triple negative tumors, has a distinct interest from having its unique behaviors regarding biological, clinical, histological, hormone receptors status, Her2/neu expression, and therapeutic modalities. We made a study on Iraqi women, with triple negative tumors, focusing on some important parameters in this group of patients, comparing our results with the others (from the world). We conclude that most of these parameters are identical except the tumor grade, where we found that it is significantly low. Results from studies done before on Iraqi women, for the same purpose, showed some differences from ours. These differences include percentage of these tumors among other types of breast tumors (our results looked less), grade of tumors (our results showed medium grade), and lymph nodes metastasis which looked less in our study.